2014
DOI: 10.2337/dc13-2484
|View full text |Cite
|
Sign up to set email alerts
|

The Lifetime Cost of Diabetes and Its Implications for Diabetes Prevention

Abstract: OBJECTIVE To assess the cost implications of diabetes prevention, it is important to know the lifetime medical cost of people with diabetes relative to those without. We derived such estimates using data representative of the U.S. national population. RESEARCH DESIGN AND METHODS We aggregated annual medical expenditures from the age of diabetes diagnosis to death to determine lifetime medical expenditure. Annual medical expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
118
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(138 citation statements)
references
References 29 publications
7
118
1
6
Order By: Relevance
“…Our risk group analysis was also consistent with a previous study (30) of diabetes prevention interventions, in which those with higher levels of fasting plasma glucose or A1C had more favorable CE ratios than those at the lower end of the prediabetes spectrum. Applying the USPSTF recommendation to those with a relatively low risk (overweight rather than obese, and one additional risk factor rather than multiple) diminishes CE because, while the costs for implementing the intervention are the same, the number of cases of diabetes and CVD averted is smaller.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our risk group analysis was also consistent with a previous study (30) of diabetes prevention interventions, in which those with higher levels of fasting plasma glucose or A1C had more favorable CE ratios than those at the lower end of the prediabetes spectrum. Applying the USPSTF recommendation to those with a relatively low risk (overweight rather than obese, and one additional risk factor rather than multiple) diminishes CE because, while the costs for implementing the intervention are the same, the number of cases of diabetes and CVD averted is smaller.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies (3,4) have shown that behavioral counseling intervention can reduce the risk of type 2 diabetes by 38-60%. A recent study (30) suggested that delaying or preventing type 2 diabetes for 10 years for a person at age 40 years might save more than $30,000 in lifetime medical spending. However, the effects of this intervention on other risk factors (i.e., lipid levels and blood pressure) are modest.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment cost increased with duration of diabetes, presence of complications, hospitalization, surgery, and insulin therapy, etc. In the study of Zhuo et al, [15] the annual medical spending for people with diabetes was $13966 which was almost double the medical expenses of people without diabetes. In our study, 69.6% of the individuals had comorbidities associated with diabetes.…”
Section: Outmentioning
confidence: 95%
“…Yeaw [9] analyzed the costs of complications in the United States in cohorts based on age and diabetes type and found that the cost of renal diseases, lactic acidosis and peritoneal dialysis were highest. Zhuo et al [10] estimated that the discounted excess lifetime medical costs for people with diabetes in the United States were $124,600, $91,200, $53,800 and $35,900 when diabetes was diagnosed at age 40, 50, 60 and 65, respectively. Condliffe, Parasuraman and Pollack [11] reported that medical expenditures for diabetes patients with comorbid hypertension and obesity were significantly higher than those of patients without these comorbidities.…”
Section: Introductionmentioning
confidence: 99%